Acupuncture in reproductive medicine. (July 2010) - So, Emily Wing Sze; Ng, Ernest Hung Yu
Acupuncture is increasingly being used in reproductive medicine. This review summarizes the evidence of acupuncture in pain relief for oocyte retrieval, improving pregnancy outcomes of in vitro fertilization treatment, management of ovulation disorders, male subfertility, primary dysmenorrhea, endometriosis and menopausal symptoms. However, most of the studies are nonrandomized uncontrolled trials, case reports or case series. For randomized controlled trials, the sample size is underpowered and blinding of assessors is lacking. Different acupuncture protocols and controls are used. These heterogeneities make it difficult to compare studies and draw any firm conclusions. Further studies should also evaluate the cost–effectiveness of acupuncture and investigate the underlying mechanism of acupuncture treatment.